Dobby2U: Online Services Laundry Management System - binti Mohd Zulkifli, Nur Aida Amira; Binti Rosli , Farah Nursyazana; Binti Esa, Nurul Azwin; Bin Omar, Abd Halim (Multidisciplinary Applied Research and Innovation, 2022)
Online Services Laundry Management System is a system that manages laundry services and provides facilities for users to order machines in the laundry and complete the management of laundry services. As the Covid-19 disease epidemic is becoming more widespread and spreading rapidly, all communities are advised to reduce social distance from each other and are advised to always be at their respective residences if there are no important matters outside. As such, it is believed that many communities have problems in the management of laundry services. The system was developed with the aim of making it easier for users to order machines in the laundry and complete the management of laundry services easily and quickly. Users only need to place an order online to order the type of size and quantity of machine they want and confirm the order only. Instead, the laundry will manage all the management of the laundry service. Admin will always update every process carried out in the system to make it easier for users to check the status of the service. In short, this system will be an alternative system for all users in the management of laundry services quickly and easily while maintaining social distance from each other.